(3MGTjI Ydi TQM Gdedhi Ydi GdSeQbfOjI aj GdGSJYGQGJs - (3eMeO Hf eMeO Hf CMeO Hf YHO GdbGOQ Hf YHO GdYRjR GdSfHGhj GdGRgQj, GdCejQ , J (B1232 (3g` s ((3YeQ CfSi Hf GdSjO eMeO GdOjH GdUbYGf GdHjQhJi s)
(3ChdgG (B:s
(3GdMeO GdMbjbi dc efc jG MejO jG eLjO CeG HYO ajbhd eMeO GdCejQ GdeUQi GdCRgQi gPG eG fQLhG Gddg ajg TQM TjNfG hTjN eTGjNfG heTGjNge GdYdGeI Gdedhi Ydi GdGSJYGQGJ s
(3BNQgG (B:s
(3bGd GdeDda QMeg Gddg JYGdi hGab GdJeGe HQMGH GdYGQa HGddg JYGdi SjOi OeQOGT GdeMeOi HeUQ GdeMQhSI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs